The Effect of Certification Benefits and Work Motivation on the Discipline of Negeri High School Teachers in Lubuk Raja District, Ogan Komering Ulu - Hartati , Yeni; Fitria, Happy; Fitriani, Yessi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to determine and describe the effect of certification allowances and work motivation on the discipline of public high school teachers in Lubuk Raja District, Ogan Komering Ulu Regency. The method used is descriptive quantitative method. The data collection technique uses a questionnaire. Based on the results of research and discussion, it can be concluded that the results of testing the first hypothesis can be concluded that there is a positive influence between the certification allowance on teacher discipline. The teacher certification allowance relationship model is significant, this is indicated by the value of the t-test = 3,539 or 35.39% greater than the t-table alpha 0.05 of 1.69552, then the results of testing the second hypothesis can be concluded that there is an influence between work motivation on teacher discipline. The teacher work motivation relationship model is significant, this is indicated by the value of the t-test = 3.539 or 35.39% greater than the t-table alpha of 1.69552. and the results of testing the third hypothesis, it can be concluded that the certification allowance and work motivation together have a positive influence on teacher discipline, with a significant value, namely the F test results obtained are 11, 339 greater than the distribution of F alpha 0.05 = 4.00 or Sig 0.000 <0.05.